Evaluation of the Accuracy of Cameriere, Modified Cameriere and Willems and Blenkin-Evans Methods for Turkish Children - Tuğçe Nur Şahin; Melike Güleç (International Dental Journal)
Objective: Age determination aims to determine an individual's physiological age without information about the individual's chronological age (CA) or in forensic situations in a way that does not cause loss of legal rights. The study aimed to evaluate the suitability of Cameriere (CM), Modified Cameriere (MCM) for Turkish children, Willems (WM), and Blenkin-Evans methods (BEM) for Turkish children. Design: A total of 616 Panoramic images of 321 female and 295 male healthy children from the Central Anatolia region aged between 6 and 14.99 years were used for the study. Individuals were grouped according to their age and gender (18 groups). Kruskal-Wallis test was used to evaluate the appropriateness of the methods, and intra- and interobserver agreement was statistically evaluated using the Intra-Interclass Correlation Coefficient (ICC) (p < .05). Results: The CA- estimated age (EA) difference was underestimated by 0.49, 0.45, and 0.20 years with MCM, WM, and BEM, respectively, and overestimated by 0.22 years with CM for girls; underestimated by 0.52, 0.43, and 0.12 years with MCM, WM, and BEM, respectively, and overestimated by 0.17 years with CM for boys (p < .005). Conclusion: If groups are evaluated separately, the closest results to CA for both sexes were obtained with CM. However, when the mean age difference for all age groups is evaluated by gender, the closest results to all individuals' CA were obtained using the BEM. Accordingly, if it is desired to modify a valid age determination method for a population, children from different provinces should be included in the sample group, especially in countries like Turkiye, where many different ethnic origins live together.